THE CORRELATION BETWEEN ENGLISH CLUB EXTRACURRICULAR ACTIVITIES AND STUDENTS PUBLIC SPEAKING SKILLS IN SENIOR AND VOCATIONAL HIGH SCHOOLS IN BANDAR LAMPUNG - Fajar Riyantika; Dian Shafwati; Khairun Nisa; Ismi Aulia Rachmani; I Ketut Yogi Ardika; Dhanissa Alifia Indrawan (JETA (Journal of English Teaching and Applied Linguistic), 2026)
English Club is one of the most popular extracurricular activities among senior and vocational high school students in Indonesia. This study aimed to investigate the correlation between students’ participation in English Club activities and their English public speaking performance among students in Bandar Lampung, Indonesia. This research employed a mixed-method approach involving questionnaires, speaking performance assessments, observations, and interviews. The participants consisted of active English Club members from several high schools in Bandar Lampung. The findings showed that most students had positive perceptions toward English Club activities, and students who actively participated in the program generally demonstrated better confidence, speaking organization, and public speaking performance. The study also found that English Club activities provided supportive environments that encouraged students to practice speaking English more confidently. However, several challenges were identified, including inconsistent schedules, nervousness during presentations, and students’ dependence on written notes while speaking. Overall, the findings suggest that English Club activities contribute positively to students’ public speaking skills and confidence.